Coping with chronic illness: A study with end-stage renal disease patients - Cassaretto, Mónica (2006)
This study identifies coping styles and strategies used by 40 end-stage renal disease patients over 20 years old who receive treatment in a general hospital in Peru. The instruments applied were a personal sociodemographic questionnaire and the Coping Inventory (Carver, Scheier & Weintraub, 1989). Results showed that emotion focused coping were most frequently used followed by problem focused coping. Planning, acceptance and positive reinterpretation-growth coping strategies were more frequently used by these patients, whereas mental disengagement, suppression of competing activities and behavioral disengagement were the less frequently used coping strategies. Other differences between coping styles and strategies and sociodemographic and medical variables were analyzed.